Enhancement of poly(L-lactide)-degrading enzyme production by Laceyella sacchari LP175 using agricultural crops as substrates and its degradation of poly(L-lactide) polymer. (September 2017) - Lomthong, Thanasak; Hanphakphoom, Srisuda; Kongsaeree, Prachumporn; Srisuk, Nantana; Guicherd, Marie; Cioci, Gianluca; Duquesne, Sophie; Marty, Alain; Kitpreechavanich, Vichien
Abstract: Optimization of the medium for poly(L-lactide) (PLLA)-degrading enzyme production in shake flask experiments was investigated using agricultural products as substrates. Cassava chips and soybean meal were the best carbon and nitrogen sources, respectively, as determined by the one-factor-at-a-time method. Enzyme production was significantly enhanced by the addition of phosphates, but was suppressed by the addition of ammonium salt. The maximum enzyme production, 65.5 U/mL, was obtained from the optimized medium consisting of 4.64 g/L cassava chips, 1.53 g/L soybean meal and 0.31 g/L PLLA powder using central composite design in the basal medium. The optimal physical factors in 3 L airlift fermenter were 50 °C, pH 7.0 and 0.5 vvm aeration rate for 18 h, yielded 94.4 U/mL. The crude enzyme was shown to be able to hydrolyze PLLA powder (91%) at 50 °C in 72 h which showed high efficiency for recycling of PLLA polymer and reducing the global environmental problem.